Analisis Warna dan Tipografi Aplikasi Siap Kerja menggunakan UCD Untuk Tingkat Kepuasan Green UI: - - Rahman, Eisya; Adelia, Adelia; Wasid, Asep; Irawan, Debi; Supriana, Fadhlanrashif Ibrahim (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study aims to analyze the impact of color, font type, and green interface design on user satisfaction in the Siap Kerja mobile application. The problem that prompted this study was the low level of user satisfaction due to the selection of colors that were uncomfortable for the eyes, font types that reduced readability, and interface designs that did not fully apply the principles of sustainability in the user experience (sustainable UI). In digital interface design, sustainability is not only related to broad environmental issues, but also includes energy efficiency and visual comfort when using the application. Before filling out the questionnaire, respondents were given a preview of the Siap Kerja application interface to assess the color elements, typography, and green interface design concept. The concept of green interface design in this study refers to the optimization of visual aspects, such as application design with dark mode, as well as the selection of visually efficient typography. This optimization not only helps reduce device power consumption but also improves user comfort and reduces eye strain. Therefore, sustainability is considered one of the characteristics of interface design, not a form of satisfaction in itself. The results of the study show that color, typography, and green interface design have a significant impact on user satisfaction, with an explanatory level of 0.84. These findings indicate that the application of sustainable UI principles can improve the quality of the user experience while supporting energy efficiency in the use of digital applications.